KEPERCAYAAN DIRI ANAK DALAM PEMBELAJARAN PENGEMBANGAN BERBAHASA PADA KELOMPOK B1 PAUD ASSALAM MUARA BANGKAHULU KOTA BENGKULU - Evi Martasari; Sri Saparahayuningsih; Delrefi Delrefi (Jurnal Ilmiah POTENSIA, 2018)
The problem in this research is how the child's self-confidence in learning language development in group B1 PAUD AssalamMuaraBangkahulu Bengkulu City. The purpose of this study was to determine the confidence of children in learning language development in group B1 PAUD AssalamMuaraBangkahulu Bengkulu City. Type of research used in this study is descriptive quantitative research. Technical Data collection using observation techniques.Data analysis using statistic with formula percentage. The result of the research shows that the Self Confidence of Children in Learning of Development of Children in Group B1 PAUD AssalamMuaraBangkahulu Bengkulu City, the result of child confidence is still enough. The details are tolerance (co-operation), optimism, decision making, and responsibility is sufficient average. Teachers should train the ability of children with learning methods of language development or teachers able to actualize the ability of children who have not developed so that the child's self-confidence is formed. To the researcher, his followers can continue this research by focusing on improvement or improvement of children's confidence, good tolerance (cooperation), optimistic, decision and responsible.